PERBEDAAN PERSEPSI TERHADAP KEPUTUSAN PEMBELIAN DALAM MEMILIH PEMBELIAN ONLINE DAN PEMBELIAN LANGSUNG (Studi Kasus Mahasiswa POLITAMA Surakarta) - Sarjana Rini, Luluk Takari; Rahayu, Bakti Sri (Surakarta Management Journal, 2021)
The purpose of this reseach to find out about differences in perception of purchasing decisions in choosing online purchases and direct purchases in polytechnic Pratama Mulia Surakarta (POLITAMA). The populations used is all students POLITAMA who have made online purchase and direct purchases. The technique used in taking this sample is purposive sampling method with a sample size of 98 respondents. The analysis shows indicate that there are significant differences between online purchases and direct purchases of purchasing decisions from cultural factors and psychological factor, and there is no significant difference between online purchases and direct purchases of purchasing decisions from social factor and personal factors and personal factors, and there is a significant difference between direct purchases and purchases of joint purchasing decisions from cultural, social,personal and psychological factor together. Keywords : cultural factors, social factors, personal factor, psychological  factors,  purchasing                    decisions.